The ABCs of chronic kidney disease. Issue 10 (October 2018) - Zuber, Kim; Davis, Jane
Abstract : ABSTRACT: Management of patients with chronic kidney disease has evolved since the last Kidney Disease Improving Global Outcomes clinical practice guideline was published in 2012. This article reviews the most recent guidelines, common management issues in primary care, kidney risk and outcome calculators, and over-the-counter medications that may cause community-acquired acute kidney injury.